The world of robert jordan's the wheel of time eaudiobook - Jordan, Robert (Wheel of Time., 2019)
Since its debut in 1990, The Wheel of Time by Robert Jordan has captivated millions of readers around the globe with its scope, originality, and compelling characters. The Wheel of Time turns and Ages come and go, leaving memories that become legend. Legend fades to myth, and even myth is long forgotten when the Age that gave it birth returns again. In the Third Age, an Age of Prophecy, the World and Time themselves hang in the balance. What was, what will be, and what is, may yet fall under the Shadow. In this series companion book, the listener will learn about the exotic beasts used by the Seanchan and hear of the rise and fall of Artur Hawking, and peruse the deeper story of the War of the Shadow. Here is the tale of the founding of the White Tower, and the creation of the Ajahs. The inner workings of the closed country, Shara, are revealed, as is the existence of a hitherto unknown continent called The Land of the Madmen.